Efficacy and safety of fluconazole prophylaxis in extremely low birth weight infants: multicenter pre-post cohort study. Issue 1 (December 2016) - Lee, Juyoung; Kim, Han-Suk; Shin, Seung; Choi, Chang; Kim, Ee-Kyung; Choi, Eun; Kim, Beyong; Choi, Jung-Hwan
Abstract Background There have been many studies supporting fluconazole prophylaxis in preterm infants for prevention of invasive fungal infections (IFIs). However, the routine use of fluconazole prophylaxis in neonatal intensive care units (NICUs) raises concerns with respect to resistance development, including the selection of resistantCandida species. We aimed to evaluate the efficacy and safety of fluconazole prophylaxis in extremely low birth weight (ELBW) infants. Methods An interventional pre-post cohort study at two tertiary NICUs was conducted. Data from two 5-year periods with and without fluconazole prophylaxis (Mar 2008–Feb 2013 and Mar 2003–Feb 2008) was compared. Prophylactic fluconazole was administered starting on the 3rd day at a dose of 3 mg/kg twice a week for 4 weeks during the prophylaxis period. Results The fluconazole prophylaxis group consisted of 264 infants, and the non-prophylaxis group consisted of 159 infants. IFI occurred in a total of 19 neonates (4.7 %) during the 10-year study period. Fluconazole prophylaxis lower the fungal colonization rate significantly (59.1 % vs. 33.9 %, P <0.001). However, the incidence of IFIs in ELBW infants was not reduced after fluconazole prophylaxis (4.4 % vs. 5.5 %, P = 0.80). Rather, although the increase did not reach statistical significance, fluconazole prophylaxis tended to increase the incidence of invasive infections involving fluconazole-resistantC. parapsilosis (0 % vs. 41.7 %, P = 0.11). Conclusions Fluconazole prophylaxis was not efficacious in decreasing IFIs in ELBW infants. There is a need for targeting prophylaxis to greatest risk population and prospective studies to measure the long-term effect of fluconazole prophylaxis on the emergence of organisms with antifungal resistance.